Development of an Extractive Reactor Block in the Aspen Plus Simulator - Ngu Ming, Tiong (2012)
The design and operation issues for extractive reactor system are considerably more complex than those involved for either conventional extraction column or convention reactors. The introduction of an in situ separation function within the reaction zone leads to complex interactions between liquid-liquid equilibrium, liquid-liquid mass transfer, intra-catalyst diffusion (for homogeneously catalysed processes) and chemical kinetics. The advantages of such alternatives is the use of simultaneous extraction and reaction to improve the yields and/or selectivity to the products, and also that they require smaller recycle flows. This research is to purpose a suitable configuration for extractive reaction by identify the important parameter that affect the process and develop the kinetic subroutine in Aspen Plus simulation. The reactor block is design by using the Aspen plus simulation to set up and specifies the application type. It is combining with an Excel spreadsheet to performance the calculations by using Dynamic Data Exchange (DDE). From the simulation, it show out that the production of for the first stream with 249.430 kmol/hr methanol, 687.099 kmol/hr fatty acid methyl ester, and 336.185 kmol/hr glycerol. However, for the second stream which produce 133.780 kmol/hr triglyceride, 137.452 kmol/hr methanol and 118.889 kmol/hr fatty acid methyl ester. For the reactor block design it is an integrate current, future technology in exciting plant and also perform plant optimization and control to improve the plant competitiveness.